2019
DOI: 10.1093/jxb/erz226
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear-localized PPR protein OsNPPR1 is important for mitochondrial function and endosperm development in rice

Abstract: Pentatricopeptide repeat (PPR) proteins constitute one of the largest protein families in land plants. Recent studies revealed the functions of PPR proteins in organellar RNA metabolism and plant development, but the functions of most PPR proteins, especially PPRs localized in the nucleus, remain largely unknown. Here, we report the isolation and characterization of a rice mutant named floury and growth retardation1 (fgr1). fgr1 showed floury endosperm with loosely arranged starch grains, decreased starch and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 88 publications
1
36
1
Order By: Relevance
“…Although the large PPR family is widely distributed among plants, only a small number of PPR proteins have been characterized. The majority of PPR proteins contain chloroplast-or mitochondrion-targeting peptides (Lurin et al 2004), and some contain nucleus-targeting peptides (Ding et al 2006;Hao et al 2019). PPR proteins commonly participate in RNA metabolism in organelles or the nucleus, and are essential for normal plant growth and development.…”
Section: Transcript Levels Of Chloroplast Ribosomal Rnas and Chloropmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the large PPR family is widely distributed among plants, only a small number of PPR proteins have been characterized. The majority of PPR proteins contain chloroplast-or mitochondrion-targeting peptides (Lurin et al 2004), and some contain nucleus-targeting peptides (Ding et al 2006;Hao et al 2019). PPR proteins commonly participate in RNA metabolism in organelles or the nucleus, and are essential for normal plant growth and development.…”
Section: Transcript Levels Of Chloroplast Ribosomal Rnas and Chloropmentioning
confidence: 99%
“…The chloroplast-localized OsPGL12 is mainly involved in the intron splicing of ndhA in chloroplasts (Chen et al 2019). The mitochondrion-localized OsFLO10 is mainly involved in the trans-splicing of the nad1 intron 1 in mitochondria (Wu et al 2019), and the nucleus-localized OsNPPR1 was reported to be involved in the intron splicing of a small number of nuclearlocalized genes, many of which are mitochondrionlocalized (Hao et al 2019). The chloroplast-localized and/or mitochondrion-localized PPR proteins, such as OsPPR1 (Gothandam et al 2005), OsOTP51, OsPPR4, OsWSL, OsALS3 (Lin et al 2015a), OspTAC2 (Wang et al 2016a), OsPPR6 (Tang et al 2017), OsSLA4, OsWSL5 and OsPGL12, are essential for early chloroplast development in rice at the seedling stage.…”
Section: Introductionmentioning
confidence: 99%
“…We found that most PPR genes showed preferential accumulation in leaves compared to other tissues, which were likely to be responsible for their subcellular localization, and most reported PPR proteins were located in mitochondria or chloroplast. A relatively high expression level was revealed in seeds, suggesting that they have potential function in seed development, which has been reported to be involved in endosperm development [14]. As shown in Figure 9, Glyma.11G008800, Glyma.13G220400 and Glyma.15G192000 showed extremely high expression in roots and root hairs, indicating that the DYW subgroup PPR genes may play specific roles in responding to drought stress.…”
Section: Resultsmentioning
confidence: 86%
“…It was reported that the nuclear OsNPPR1 encoded a PPR protein, which was involved in the Regulation of mitochondrial development and endosperm development. The mutant named fgr1 exhibited a lower content of starch and delayed seedling growth [14]. Rice PPS1 encodes a DYW motif-containing PPR protein, which is important for C-to-U RNA editing of nad3 transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…PPR proteins have been found to exhibit RNA-binding properties, which facilitate in mediating gene expression through posttranscriptional processes associated with transcripts in the mitochondria, chloroplast, and nucleus. Thus, PPR genes are thought to have a major impact on organelle stability, including biogenesis, and function through their involvement in various posttranscriptional processes such as RNA-editing [ 1 , 8 ], RNA-splicing [ 9 ], and RNA-processing [ 10 ].…”
Section: Introductionmentioning
confidence: 99%